2005
DOI: 10.1210/en.2004-1085
|View full text |Cite
|
Sign up to set email alerts
|

Y2 Receptor-Selective Agonist Delays the Estrogen-Induced Luteinizing Hormone Surge in Ovariectomized Ewes, but Y1-Receptor-Selective Agonist Stimulates Voluntary Food Intake

Abstract: Neuropeptide Y (NPY) plays a major role in the regulation of food intake, regulation of homeostasis, and neuroendocrine function. We have previously shown that third ventricular infusion of this peptide delays the estradiol benzoate-induced surge in LH secretion in ovariectomized ewes. To determine the receptor subtype that transmits this effect, we have now used the same model to infuse a Y1 receptor agonist [NPY Leu31 Pro34], a Y2 receptor agonist (PYY3-36), and a Y4 receptor agonist (pancreatic polypeptide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 66 publications
2
17
0
1
Order By: Relevance
“…In this sense, we propose that GnIH may function as a molecular switch, between the two functions. This is consistent with the actions of a number of other peptides, which have opposing actions on reproduction and feeding, including NPY [40] and melanocortins [41], amongst others.…”
Section: Discussionsupporting
confidence: 82%
“…In this sense, we propose that GnIH may function as a molecular switch, between the two functions. This is consistent with the actions of a number of other peptides, which have opposing actions on reproduction and feeding, including NPY [40] and melanocortins [41], amongst others.…”
Section: Discussionsupporting
confidence: 82%
“…Although NPY is a negative regulator of the reproductive axis in the ewe [9], the gene expression data and peptide data presented herein suggest that the GnRH/LH response to leptin treatment in lean hypogonadotropic animals is not explained by a reduction in the level of this peptide.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the so-called ‘appetite-regulating peptides’ also regulate reproductive function, acting within the brain [6] to regulate gonadotropin-releasing hormone (GnRH) secretion [7]. Neuropeptide Y (NPY), agouti-related peptide (AgRP), and melanocortins are examples of peptides with such dual functions [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…However, as NPY terminals are known to synapse on GnRH perikarya in the sheep [22, 23, 33, 51], it is reasonable to speculate that GnRH neurons may be receptive for NPY. Several subtypes of NPY receptors, including NPY-Y 1 , NPY-Y 2 and/or NPY-Y 5 , have been linked with a modulation of GnRH secretion in rats [60,61,62], and, more recently in sheep [63]. In rats, the coexistence of GnRH and NPY-Y 5 immunoreactivity was also demonstrated at the level of the soma [62], but NPY-Y 1 and NPY-Y 2 receptors appeared to be involved in the control of GnRH secretion at the level of the median eminence [60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the coexistence of GnRH and NPY-Y 5 immunoreactivity was also demonstrated at the level of the soma [62], but NPY-Y 1 and NPY-Y 2 receptors appeared to be involved in the control of GnRH secretion at the level of the median eminence [60, 61]. In sheep, recent findings using specific receptor subtype agonists suggested that NPY-Y 2 receptors have probably a larger influence on GnRH secretion than NPY-Y 1 , which may be involved in food intake [51, 63]. We are currently determining if GnRH neurons express NPY receptors in the ovine brain.…”
Section: Discussionmentioning
confidence: 99%